2003
DOI: 10.1002/jclp.10191
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits predicting long‐term adjustment after surgery for ulcerative colitis

Abstract: Very few studies have examined the relationship between personality traits and long-term postoperative psychosocial adjustment. In a sample of 46 patients, we examined the relation between personality traits before pelvic pouch surgery for ulcerative colitis and psychosocial adjustment seven years postoperatively, controlling for the effects of surgical functional outcome. The Karolinska Psychodynamic Profile (KAPP) was used for personality assessment. Surgical functional outcome scales and the Psychosocial Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…There are also 2 studies that found a relationship between personality traits and psychosocial adjustment in patients undergoing surgery for UC 28,29 or CD. 30 Our study focused on unselected IBD patients, whereas the studies by Weinryb et al 28,29 and Post et al 30 considered the QoL in a selected group of patients who had undergone surgery for treatment of IBD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are also 2 studies that found a relationship between personality traits and psychosocial adjustment in patients undergoing surgery for UC 28,29 or CD. 30 Our study focused on unselected IBD patients, whereas the studies by Weinryb et al 28,29 and Post et al 30 considered the QoL in a selected group of patients who had undergone surgery for treatment of IBD.…”
Section: Discussionmentioning
confidence: 95%
“…30 Our study focused on unselected IBD patients, whereas the studies by Weinryb et al 28,29 and Post et al 30 considered the QoL in a selected group of patients who had undergone surgery for treatment of IBD. One explanation could be that personality might play an important role in the way in which one deals with a stressful situation such as a surgery, but other variables would be more relevant in the long-term adaptation to a chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64] A few studies have reported differences in personality traits according to IBD type, with CD patients being significantly more extroverted and having higher psychoticism personality scores than UC patients, but neuroticism scores were similar. 62,65 Personality traits have not been addressed in the pediatric HRQOL literature.…”
Section: Personality Traitsmentioning
confidence: 94%
“…The profile consisted of 18 subscales, and ratings were made from the information obtained through a semi-structured interview procedure. The KAPP has been shown to be reliable and useful for assessing fairly stable character traits, and that it can discriminate between patients with and without psychiatric psychopathology (Weinryb, Gustavsson, & Barber, 2003).…”
Section: Psychodynamic Variablesmentioning
confidence: 99%